Analysis of numeracy literacy skills in elementary school students - Siti Maysarah; Dian Armanto; Izwita Dewi; Sahat Saragih (State Islamic University of North Sumatra, 2024)
This study analyzes students' numeracy literacy skills at the middle level (levels 3 and 4). The research subjects comprised three students from SDN (elementary school) 106831 Bakaran Batu, Deli Serdang Regency, representing varying initial math abilities (high, medium, and low). Student groupings were based on data from mathematics test scores. The research follows a descriptive qualitative approach using Sugiyono's methodology. The research instrument employed was a mid-level numeracy literacy ability test (level 3 and level 4), which included questions assessing cognitive processes related to application and reasoning, as well as interview guidelines. Data analysis techniques involved data reduction, presentation, and conclusion. The study revealed that highly skilled students demonstrated proficiency in level 3 (application) and level 4 (reasoning) numeracy literacy. However, students with moderate and low abilities struggled to understand questions at these levels. Common student errors included failing to record relevant information from the questions, making mistakes in problem-solving processes, and neglecting to document their answer conclusions. The main factor hindering students' ability to answer moderate-level numeracy literacy questions appears to be their lack of familiarity with word problems related to everyday life. Additionally, students have difficulty grasping the relationship between concepts presented in contextual problems.